SCJA Sun certified Java associate : study guide (exam CX-310-019) - Liguori, Robert (McGraw-Hill, 2010)
Includes hundreds of practice questions and hands-on exercises; this comprehensive study guide covers what you need to know--and shows you how to prepare--for the challenging SCJA Exam CX-310-019. --